Peran Guru Muatan Lokal Keagamaan Dalam Peningkatkan Kemampuan Membaca Al-Qur’an Pada Siswa di SMP Negeri 1 Mojoagung - Muhammad Ali Hasan; Moh Kholik; Nurul Lailiyah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
This study aims to describe the role of Religious Local Content teachers in Improving Students' Al-Qur'an Reading Ability at SMPN 1 Mojoagung in the 2021 academic year. Based on the data obtained through interviews, observations, and documentation, it can be concluded that: The role of the teacher Religious Local Content in improving the ability to read the Qur'an at SMPN 1 Mojoagung. The teacher's role in Improving the Ability to Read Al-Qur'an consists of 3 aspects: first, the teacher as a supervisor of this task and responsibility places more emphasis on planning and implementing teaching. Second, the teacher as a leading worker is to put pressure on the task and provide guidance in the form of assistance to students in solving the problems they face. Third, the teacher as the class administrator, and class manager, and Fourth, the teacher as a motivator. The methods and techniques used by teachers of local religious content in improving the ability to read Al-Qura'an at SMPN 1 Mojoagung are the tilawati method and the qiroati' method. The supporting factors for the role of local religious content teachers in improving students' reading skills of the Qur'an consist of parents and local content teachers, namely focusing on being their guide when reading the Qur'an. In addition, the teacher also always accompanies, directs and always supervises. The inhibiting factor for the role of the Religious Local Content teacher in improving the ability to read the Al-Qur'an is electronics such as cellphones which always make children lazy to read the Qur'an. In addition, another inhibiting factor is the community when students choose the wrong way to get along. This method is reading the Qur'an which directly includes and practices tartil reading in accordance with the rules of Tajweed science in the education system and the teaching of the Qiro'at method through a student-centered education system.